Analysis of the Application of the Accurate Accounting System in the Recording of Financial Statements of PT. The Great Ocean Ocean - Selly Febriana; Rahmat Daim Harahap (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
The Accurate Accounting System is a software tool used by companies to prepare computerized financial reports. This study takes the title Analysis of the Application of Accurate Accounting Systems in the Recording of Financial Statements of PT. The Great Ocean Ocean. This research uses descriptive qualitative method. This study aims to determine how the application of the Accurate Accounting System. Research conducted by the author is a shipping company. This company already uses an Accurate Accounting System in inputting the company's financial statements. The results of this study are that in implementing the Accurate Accounting System there are no obstacles or problems, so it can still make it easier for employees to input financial reports. In implementing an Accurate Accounting System in this company, there are several advantages that are known by researchers. Therefore researchers conducted research on the application of Accurate Accounting Systems in companies.